Cross-correlated humidity-dependent structural evolution of Nafion thin films confined on a platinum substrate. Issue 5 (3rd January 2020) - Shrivastava, Udit N.; Suetsugu, Kota; Nagano, Shusaku; Fritzsche, Helmut; Nagao, Yuki; Karan, Kunal
Abstract : We cross-correlate the hydration-dependent structure and properties – microscopic and macroscopic – of a thin Nafion ionomer film on an electrochemically pertinent Pt substrate. Abstract : Nanometer thin films of Nafion ionomer interfaced with platinum form the functional electrodes in many electrochemical devices including fuel cells and electrolyzers. To impart facile proton conduction in a Nafion ionomer, sufficient hydration of the Nafion ionomer is necessary to create a percolating network of water-filled nanometer-sized hydrophilic domains that manifest as macroscopic swelling. This hydration behavior of the ionomer thin films is poorly understood especially for films confined on electrochemically relevant Pt substrates. In this work, we present the evolution of hydration-dependent microscopic hydrophilic domains and macroscopic expansion of a 55 nm thin Nafion film on a Pt substrate. The cross-correlation among the film macro-expansion from ellipsometry, the micro-expansion from GISAXS, and the water distribution from neutron reflectometry (NR) explains the observed non-affine behavior of the film which can be attributed to the randomly and spatially non-uniform distribution of water domains. A correlation between the macroscopic factor ( ε / τ ) for protonic conductivity, and the domain size and swelling is presented for the first time. In addition, interfacial water between Pt and the ionomer interface is estimated at 75% and 84% RH, and an increase in domain size with RH is discussed to explain the increased activity and oxygen diffusivity with RH.